Efektivitas Penyelenggaraan Program Dana Hibah Pemerintah Provinsi Sumatera Utara - Tree Engel Natalia (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research aims to find out whether the North Sumatra Provincial Government (Pemprov) grant funding program is effective. Problem formulation: How enthusiastic the community is in responding to the program. Research objective: To find out how enthusiastic the community is in responding to the program. The data collection methods used in this research are decision techniques and direct research in the field. The technical analysis used is the description method, namely a method carried out by analyzing things related to grant funding assistance.